(untitled) (Research, Society and Development, 2021)
The regeneration and succession processes that occur in native forests allow the continuity of species and provide information about their structure and distribution in forest communities. These processes are closely related to the degree of vegetation exploitation, edaphoclimatic factors and also to the preservation of forest remnants. This work aimed to verify the occurrence of individuals of A. colubrina and its distribution in the different diametric classes in the caatinga area at Fazenda Lameirão, municipality of Santa Terezinha-PB. The method used for counting and measuring height and diameter of individuals of this species A. colubrina was walking. During the route, all individuals of A. colubrina found in the route were measured circumference at breast height (CAP) <6 cm, and total height, using a tape measure (cm) and graduated ruler (GR 500 professional) (cm), respectively. The values obtained from the circumferences were transformed into diameters (CAP / π), and from these, the difference between these values was obtained and the interval between the diametric classes was established. 99 individuals were inventoried, most of which had a height greater than 5 m and an average DBH 14.33 cm. According to the DAP values obtained, the specimens were distributed in five diametric classes with an amplitude of 5.73 cm in each class. The largest number of individuals was concentrated in classes II and III. A. colubrina occurs in an agglomerated form. The greater number of individuals in the first three diametric classes, indicates a high recruitment of juvenile individuals in these classes.